Enterprise feedback management (EFM): what lies beyond the hype?. (28th July 2020) - Aksoy, Lerzan; Benoit, Sabine; Joag, Shreekant G.; Kandampully, Jay; Keiningham, Timothy Lee; Yan, An L.
Abstract : Purpose: The needs of CMOs to utilize a firm's data productively in order to support decision-making combined with the reported benefits of enterprise feedback management solutions has resulted in a rapid rise in usage and valuation of EFM providers. The explicit promise of EFM providers is improved financial performance, whereas there is no scientific research investigating this link. To investigate the link between EFM usage and financial performance is core of this research. Design/methodology/approach: To gain insight into this link survey data from 127 US-based firms on their usage of EFM platforms was linked to their stock market performance over several years. Findings: This research did not find any significant positive relationships between different aspects of EFM usage investigated and stock returns. It is important to note that these results should not be taken as validation that EFM systems do not result in positive financial outcomes for firms. It may be that superior market performance as measured through stock returns is difficult to observe through a cross-sectional analysis. Instead these results indicate that superior market performance as measured through stock market performance is not an obvious, generalizable outcome for firms that have adopted EFM systems. Originality/value: EFM has rapidly grown across many consumer facing industries, with EFM platform providers receiving very high market valuations on relatively small revenue streams. This is one of the first scientific papers to study the usage and impact of these EFM systems.